2016
DOI: 10.12957/epp.2016.24839
|View full text |Cite
|
Sign up to set email alerts
|

Dependência de internet e habilidades sociais em adolescentes

Abstract: Este estudo teve como objetivo verificar a associação entre as habilidades sociais (HS) e a dependência de internet (DI), a associação entre variáveis sócio-demográficas e HS, assim como constatar as variáveis preditoras da DI, em uma amostra composta por 482 escolares selecionados aleatoriamente em um município do Rio Grande do Sul, Brasil. Foram utilizados os seguintes instrumentos: Inventário de Habilidades Sociais para Adolescentes e o Internet Addiction Test. Os resultados indicaram que os adolescentes de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
15

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 27 publications
0
13
0
15
Order By: Relevance
“…The Internet is a complementary tool of social interaction, since in adolescence, peer relationships are fundamental for healthy development. However, the authors point out that online social networks should not replace face-to-face relationships (15) .…”
Section: Discussionmentioning
confidence: 99%
“…The Internet is a complementary tool of social interaction, since in adolescence, peer relationships are fundamental for healthy development. However, the authors point out that online social networks should not replace face-to-face relationships (15) .…”
Section: Discussionmentioning
confidence: 99%
“…Different national and international studies have sought to identify the positive and negative impact of the ICTs' use by adolescents. The negative bias detected by the interaction of adolescents with different ICTs is pointed out by internet abuse and dependence, few physical activities, reduced concentration and memory skills, contact with pornography, violent content and the possibility of finding inconvenient people (Issa & Isaias, 2016;Terroso & Argimon, 2016). On the other hand, the positive bias is addressed by a study in Australia and Portugal with 265 adolescents, which identified new factors that favor the use of the Internet, such as problem solving skills, proactive study, improved communication and collaboration with peers and family, as well as the incentive to play virtual and physical games (i.e., Wii® and Kinect for Xbox®) (Issa & Isaias, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Também está ligada às habilidades sociais, da qual ainda não existe um consenso exato para a sua definição, porém entende-se como comportamentos e relações com os demais. Trata-se de comportamentos padronizados para uma interação, onde estão associados ao modo de pensar, agir e falar, não permitindo uma relação negativa diante da sociedade (Terroso & Argimon, 2016).…”
Section: Introductionunclassified